Aristotle and Modern Constitutionalism. (September 2022) - Duke, George
Abstract : Any attempt to apply Aristotelian political categories to the principles of modern constitutionalism is undoubtedly at risk of anachronism. This paper acknowledges non-trivial differences between the Ancient Greek politeia, as theorised by Aristotle, and the modern constitution. It nonetheless argues that the central principles of the modern liberal constitution can be elucidated within the explanatory frame of the Aristotelian concept of the politeia as a political determination of institutional structures and competences oriented by an interpretation of the public good. The paper is divided in three sections. Section 1 outlines Aristotle's account of the politeia . Section 2 considers some central principles of modern constitutionalism. Section 3 then examines these principles under an Aristotelian lens. The conclusion sketches a potential objection, implicit in the paper's arguments, to a recent proposal for a 'neo-Aristotelian' normative constitutional theory.